Some Binomial Sums of \(κ\)-Jacobsthal and \(κ\)-Jacobsthal-Lucas Numbers - Godase, A. D. (Communications in Mathematics and Applications, 2023)
In this paper, we formulate some crucial identities containing \(κ\)-Jacobsthal and \(κ\)-Jacobsthal-Lucas numbers and use these identities to establish some binomial sums of \(κ\)-Jacobsthal and \(κ\)-Jacobsthal-Lucas numbers.